College Students' Experiences of Race-Related Bias or Hatred in Their Lifetimes and COVID-19 Era. Issue 3 (May 2021) - Shah, Gulzar H.; Rochani, Haresh D.; Telfair, Joseph; Ayangunna, Elizabeth; Skuraton, Gemma
Abstract : Objective: The primary aim of this study was to investigate whether students in minority race categories are more likely to experience race-related bias and hatred in their lifetime and since the onset of COVID-19, after controlling the effect of demographic and other variables. Methods: This quantitative study used primary data from the survey of 1249 college students at one of the universities in Georgia during April and May 2020. We performed multinomial logistic regression, computing 2 models for the 2 ordinal dependent variables concerning students' experience of race-related bias and hatred—( a ) during their lifetime and ( b ) since the onset of COVID-19 in March 2020—both measured as "never, " "rarely, " "sometimes, " and "fairly often or very often." Results: During their lifetime, 47.5% of students had experienced some level of bias or hatred, ranging from "rarely" to "very often." Since the onset of COVID-19 on March 2 in Georgia, in a short period of 1 to 2 months, 17.6% of students reported experiencing race-related bias or hatred. Univariate statistics revealed substantial differences in race-related bias and hatred by race, experienced during students' lifetime as well as since the onset of COVID-19. Results of multinomial logistic regression showed that the odds of having experienced bias or hatred during their lifetime were significantly higher ( P < .05) for the Black students than for White students (adjusted odds ratio [AOR] = 75.8, for very often or often vs never; AOR = 42 for sometimes vs never). Compared with White students, the odds of hatred and bias were also significantly higher for students who were Asian, multiple races, or another non-White race. The odds of having experienced race-related bias and hatred since the onset of COVID-19 were also higher for Black Asian, multiple races, and other non-White students. Conclusions: This study adds critical scientific evidence about variation in the perception of bias and hatred that should draw policy attention to race-related issues experienced by college students in the United States. Abstract : Supplemental Digital Content is Available in the Text.